1997
DOI: 10.1021/np960513c
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds from Taiwania cryptomerioides

Abstract: Two new sesquiterpenes, 10 alpha-hydroxyamorphan-4-en-3-one (1) and 4 alpha-methylcadinane-4 alpha-methyl-1 alpha,2 alpha,10 alpha-triol (2), together with four known compounds, sesquiterpenes 10 alpha-hydroxycadinan-4-en-3-one (3) and alpha-cadinol (4), diterpene ferruginol and lignan helioxanthin, were isolated from the whole plant of Taiwania cryptomerioides under bioassay-guided fractionations. The structures of 1 and 2 were elucidated mainly by the NMR spectroscopic analyses. Bioactivities of the isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 12 publications
6
66
0
1
Order By: Relevance
“…The coupling constant of 6.3 Hz between H-5 and H-6 provided evidence for the cis-fusion: in trans-fusion, H-5 appeared as a broad singlet, while for cis-fusion, H-5 resonated as a doublet with a coupling constant of 6.5 Hz. 8 Since H-6 appeared as a doublet of doublets of doublets with the large coupling (J ) 10.2 Hz) and the smallest coupling (J ) 5.1 Hz) constants with H-7 and H-1, respectively, H-6 and the 7-isopropyl substituent were located at the -axial and -equatorial positions, respectively. Irradiation of H ax -6 produced signal enhancement of H eq -1 and 10-OMe, supporting the assignment of cis-fusion and also indicating the location of 10-OMe at the -axial position, cis to both H eq -1 and H ax -6.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The coupling constant of 6.3 Hz between H-5 and H-6 provided evidence for the cis-fusion: in trans-fusion, H-5 appeared as a broad singlet, while for cis-fusion, H-5 resonated as a doublet with a coupling constant of 6.5 Hz. 8 Since H-6 appeared as a doublet of doublets of doublets with the large coupling (J ) 10.2 Hz) and the smallest coupling (J ) 5.1 Hz) constants with H-7 and H-1, respectively, H-6 and the 7-isopropyl substituent were located at the -axial and -equatorial positions, respectively. Irradiation of H ax -6 produced signal enhancement of H eq -1 and 10-OMe, supporting the assignment of cis-fusion and also indicating the location of 10-OMe at the -axial position, cis to both H eq -1 and H ax -6.…”
Section: Resultsmentioning
confidence: 98%
“…9 The 1 H and 13 C NMR and DEPT data revealed that 9 had the skeleton of a cadinane type sesquiterpene. 8,9 Comparison of these data with those of 10R-hydroxyamorphane-4-en-3-one 8,10 indicated that the hydroxyl group of 10R-hydroxyamorphane-4-en-3-one was replaced by an O-methyl group in 9. This demonstrated that the methoxyl group was located at C-10, which was proved by an HMBC correlation between the methoxy protons and C-10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Labbe et al (1993) demonstrated that T-cadinol shows significant toxicity to Artemia salina (brine shrimp bioassay). He et al (1997) reported that a-cadinol showed bioactivity against brine shrimp, yellow fever mosquito (Aedes aegypti) larvae, and human tumor cells . Similarly, in previous studies we found that a-cadinol was moderately active against HT-29, and T-muurolol was modestly active against both the HT-29 and MCF-7 cell lines (Chang et al 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…Helioxanthin (10), an arylnaphthalene derivative, was identified earlier from the root of this species 52 and from thirteen other plants. 89,148,[157][158][159][160][161][162][163][164][165][166][167] The dibenzylbutyrolactone helianthoidin was isolated previously 53 …”
Section: Structure Elucidation Of the Isolated Compoundsmentioning
confidence: 99%